Analisis Kadar Glukosa Pada Tepung Umbi Amorphophallus sp. - Syamsiah, .; Hartati, . (Fakultas MIPA UNM, 2010)
This research purpose to know the impact of long fermentation with yeast to suweg tuber to know the value of dissolve glucose. The dissolve glucose between times of fermentation about 24 hours, 48 hours and 72 hours. This research used free variable which was long fermentation and bound variable is glucose value of flour in suweg tuber fermentated. To know the impact of this research, used the